Menjaga Stabilitas Air Tanah di Kota Pantai - Hartono Hartono (Jurnal Proyek Teknik Sipil, 2022)
Abstract : Water is a human need for daily life, to meet water needs it can be from PAM or from ground water sources. With the demand for water that continues to increase with increasing population growth, there will be a shortage of water, especially groundwater. So it is necessary to maintain the availability of ground water sources, or maintain the stability of groundwater, namely by making roads, parking lots that can absorb or absorb water into the soil, increase reforestation and make infiltration wells and biopori holes so that rainwater is not directly discharged into the river or sea but is channeled. into the ground, so that groundwater remains stable or maintained.Keyword: Infiltration well.